Gadung Flour Innovation for Enhancing the Value Added of Charcoal Waste Briquettes in KUPS Maju Lestari - Marhaini; Lulu Yuningsih Mustopa; Innike Abdillah Fahmi; Anisa; Dyah Rofi'ah Rahmawati (Altifani Journal: International Journal of Community Engagement, 2025)
KUPS Maju Lestari has been producing charcoal, which generates charcoal waste that can be utilized for briquette production. However, several constraints remain, particularly in terms of production processes and equipment. This community service activity aimed to increase the value added of charcoal waste through product diversification into environmentally friendly charcoal briquettes. The target group of the activity was the Social Forestry Business Group (KUPS) Maju Lestari in Jajaran Baru Village, Musi Rawas Regency. The implementation methods included socialization, training, and assistance in briquette production. The results showed that participants were able to process charcoal waste into briquettes using gadung flour as a binding agent, which can be used for household needs or sold as a commercial product. Furthermore, this program is expected to increase community income and support sustainable forest management.